Reading Comprehension Through Text Structure Instruction: Does It Work? - Le, Thien Thanh Phuong; Cao, Thi Phuong Dung (OKARA: Jurnal Bahasa dan Sastra, 2025)
In English as a foreign language (EFL) contexts, reading plays a key role in academic success. However, many learners struggle with complex academic texts (or expository texts) due to limited strategic reading skills. Text structure instruction offers a promising solution by enabling learners to recognize and process textual organization through strategies such as identifying structural patterns, interpreting signal words, and summarizing with graphic organizers. This study investigated the impact of a 10-week text structure instruction program on students' reading comprehension, aiming to determine whether explicit instruction in text structure could enhance comprehension more effectively than traditional methods. A quasi-experimental design was used, with one group receiving traditional reading instruction and the other exposed to text structure instruction. Both groups completed pre- and post-tests to assess gains in reading comprehension. Results showed significant improvement in both groups, with the experimental group demonstrating a greater increase in scores. These findings suggest that structured instruction in text structure is more effective in improving reading comprehension than traditional approaches. The study highlights the value of incorporating text structure into reading instruction to better support language learners.